Meta‐analysis of three‐in‐one single capsule bismuth‐containing quadruple therapy for the eradication of Helicobacter pylori. Issue 2 (14th February 2019) - Nyssen, Olga P.; McNicholl, Adrian G.; Gisbert, Javier P.
Abstract: Background: Bismuth‐containing quadruple therapy has been suggested as first‐line and rescue alternative for Helicobacter pylori eradication. Our objective was to perform a meta‐analysis evaluating the efficacy and safety of single capsule Pylera ® (bismuth, metronidazole, and tetracycline) plus a proton‐pump inhibitor (PPI) in any line of treatment. Methods: Studies were selected up to October 2018. Outcomes were eradication and adverse events (AEs) rates pooled using the generic inverse variance method. Results: In total, 30 studies (6482 patients) were included in the systematic review. The intention‐to‐treat (ITT) efficacy was 90% (95% CI: 87%‐92%, 21 studies, I 2  = 88%) in first‐line therapy, 89% (95% CI: 86%‐93%, 12 studies, I 2  = 78%) in second‐line and 82% (95% CI: 78%‐87%, nine studies, I 2  = 60%) in third‐line; with no differences by the type or dosage of PPI used. For metronidazole‐resistant infection, the ITT efficacy as first‐line therapy was 93% (95% CI: 90%‐96%, six studies, I 2  = 0%). In second‐line therapies where patients had been previously treated with clarithromycin, the ITT efficacy was 90% (95% CI: 87%‐93%, 11 studies, I 2  = 78%). The overall incidence of AEs was 43% (95% CI: 35%‐50%, 24 studies, I 2  = 92%) and they were mostly mild. In nearly 3% of the cases, treatment was interrupted due to AEs. Conclusions: A 10‐day treatment with Pylera ® achieved an effective eradication rate of approximately 90% both in first‐ and second‐line therapy. This applies regardless of the type and dose of the PPI, in patients with clarithromycin‐ or metronidazole‐resistant strains, and in those previously treated with clarithromycin.